Profitabilitas, Utang, dan Kinerja Keuangan di Bank-Bank Indonesia: Peran Moderasi Tata Kelola Perusahaan yang Baik - Khansa Shabihah; Mutamimah Mutamimah; Dedi Rusdi; Revy Amyneva Gulnoria (Lembaga Yasin AlSys, 2026)
Financial performance is a key indicator of success for banking institutions, particularly in the context of managing profitability, debt structure, and the implementation of Good Corporate Governance (GCG). Although numerous studies have highlighted the role of financial performance in sustaining banking competitiveness, empirical research that specifically examines the effects of profitability and debt on financial performance while considering the moderating role of GCG quality in the Indonesian banking sector remains limited. This study aims to analyze the influence of profitability and debt on financial performance and to assess the role of GCG quality as a moderating variable in these relationships for banks listed on the Indonesia Stock Exchange over the 2010–2023 period. The study employed a quantitative approach using secondary data from financial reports, yielding 266 observations selected through purposive sampling. Data were analyzed using multiple linear regression with the aid of SPSS software. The results show that profitability, measured by Return on Assets (ROA), does not have a significant effect on financial performance, which is measured by Return on Equity (ROE), whereas debt, measured by the Debt to Equity Ratio (DER), has a positive and significant effect on financial performance. In addition, GCG quality, proxied by the presence of the Sharia Supervisory Board (Dewan Pengawas Syariah, DPS), has a positive effect on financial performance and strengthens the relationships between the financial variables and firm performance. These findings underline that appropriate debt management and high-quality GCG implementation are critical factors in enhancing banks’ financial performance. The implications of this study encourage banking management to continuously strengthen corporate governance in order to support long-term improvements in financial performance.